Genome sequence and genetic diversity analysis of an under-domesticated orphan crop, white fonio (Digitaria exilis). Issue 3 (12th March 2021) - Wang, Xuewen; Chen, Shiyu; Ma, Xiao; Yssel, Anna E J; Chaluvadi, Srinivasa R; Johnson, Matthew S; Gangashetty, Prakash; Hamidou, Falalou; Sanogo, Moussa D; Zwaenepoel, Arthur; Wallace, Jason; de Peer, Yves; et al.
Abstract: Background: Digitaria exilis, white fonio, is a minor but vital crop of West Africa that is valued for its resilience in hot, dry, and low-fertility environments and for the exceptional quality of its grain for human nutrition. Its success is hindered, however, by a low degree of plant breeding and improvement. Findings: We sequenced the fonio genome with long-read SMRT-cell technology, yielding a ∼761 Mb assembly in 3, 329 contigs (N50, 1.73 Mb; L50, 126). The assembly approaches a high level of completion, with a BUSCO score of >99%. The fonio genome was found to be a tetraploid, with most of the genome retained as homoeologous duplications that differ overall by ∼4.3%, neglecting indels. The 2 genomes within fonio were found to have begun their independent divergence ∼3.1 million years ago. The repeat content (>49%) is fairly standard for a grass genome of this size, but the ratio of Gypsy to Copia long terminal repeat retrotransposons (∼6.7) was found to be exceptionally high. Several genes related to future improvement of the crop were identified including shattering, plant height, and grain size. Analysis of fonio population genetics, primarily in Mali, indicated that the crop has extensive genetic diversity that is largely partitioned across a north-south gradient coinciding with the Sahel and Sudan grassland domains. Conclusions: We provide a high-quality assembly, annotation, and diversity analysis for a vital African crop. The availability of this information should empower future research into further domestication and improvement of fonio.